Building secure elections: e-voting, security, and systems theory - Moynihan, Doland P. (2004)
The increased use of information technology promises to revolutionize both the provision of government services and the vibrancy of democracy. In the aftermath of the Florida voting controversy during the 2000 presidential election, governments have placed their faith in technology, adopting e-voting because of the severity of consequencies if failure occurs and the loss of transparency traditionally associated with the voting process. A more useful theoretical guide is systems theory, which deals with complex, high-risk systems. This literature has been largely overlooked by adopters of e-voting technology, even though the practical criticisms of e-voting made by computer security specialists reflect an essentially systems theory perspective. - Reproduced.
Keywords: Elections